The impact of early foreign language learning on language proficiency development from middle to high school. (June 2022) - Jaekel, Nils; Schurig, Michael; van Ackern, Isabelle; Ritter, Markus
Abstract: Early foreign language instruction has become the norm across Europe. Expected benefits for students include linguistic advantages and ease of learning the second language (L2). However, research rarely supports these assertions. The present study investigated the receptive skills of two cohorts of English as a Foreign Language (EFL) learners in Years 5, 7, and 9 in Germany. The cohorts differed in their age of EFL onset in elementary school and, consequently, in the amount of exposure before secondary school. Linear mixed model analyses were employed to account for the hierarchical structure of the data. Learners with an earlier start performed better in Years 5 and 9 than late starters, suggesting possible long-term benefits of an earlier start. In Year 7, late starters scored higher on the proficiency assessment. Across the Year 5–9 span, the effects of learner characteristics' on English proficiency remained stable for gender, L1, grades, cognitive abilities, and cultural capital. Highlights: Earlier starters performed better in English reading and listening in Years 5 and 9 compared to late starters. Late starters performed better in Year 7. Non-linear Interaction of age of onset in school across Years 5–9. Effects of learner characteristics' on English proficiency stable across Years 5–9. Shift in the social background characteristics in secondary education.